2016
DOI: 10.5957/jsr.2016.60.1.30
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Trim Optimization for a Container Ship Based on Effects due to Resistance

Abstract: The objective of this paper is to perform trim optimization on a 4250-TEU container ship based on the influence of trim on the resistance by using computational fluid dynamics (CFD) in conjunction with towing tank tests. First, the International Towing Tank Conference (ITTC) procedures were applied to uncertainty analysis of CFD and the CFD procedure was further verified and validated through three representative resistance curves obtained by the tests. Next, a series of resistance curves in different conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Lokukaluge et al [13] studied the identification of the optimal trim with ship performance and navigation data, and concluded that selecting proper trim conditions could improve the log speed or reduce the fuel consumption of a ship. Sun et al [14] conducted a trim optimization study for a container ship using CFD and towing tank experiments, which demonstrated the significant impact of trim adjustments on reducing ship resistance and fuel consumption, offering an effective strategy for energy saving and emission reduction in real ship operations. Coraddu et al [15] researched the problems of accurate fuel consumption prediction based on data measured by onboard automation systems, and made a detailed comparison of three fuel consumption predicting models, and finally came to the conclusion that the gray box model is the best solution to obtain the optimal trim for a ship in real operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lokukaluge et al [13] studied the identification of the optimal trim with ship performance and navigation data, and concluded that selecting proper trim conditions could improve the log speed or reduce the fuel consumption of a ship. Sun et al [14] conducted a trim optimization study for a container ship using CFD and towing tank experiments, which demonstrated the significant impact of trim adjustments on reducing ship resistance and fuel consumption, offering an effective strategy for energy saving and emission reduction in real ship operations. Coraddu et al [15] researched the problems of accurate fuel consumption prediction based on data measured by onboard automation systems, and made a detailed comparison of three fuel consumption predicting models, and finally came to the conclusion that the gray box model is the best solution to obtain the optimal trim for a ship in real operations.…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, the existing literature primarily focuses on the methods to obtain optimal trim, such as CFD numerical stimulation [16,[18][19][20][21], model tests [22], and analysis of real ship measured data [12][13][14][15]17], etc. The relevant research was mostly aimed at finding the optimal trim which corresponds to the minimum energy consumption at a given draft and speed, or at performing trim and speed joint optimization with a fixed draft.…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al [9] explained the methodology for studying the effect of the trim on the resistance of the ship and applied the RANSE method for investigating this in model scale, showing good agreement between the CFD method and experimental results. Sun et al [10] conducted trim optimisation on a 4250-TEU container ship using the RANSE method at full scale. The results showed good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have modified the approximate methods for different ship types and working conditions [1][2][3]. With the development of computer technology, computational fluid dynamics (CFD) technology has been more and more used in ship performance calculation [4][5][6][7][8]. Compared with the traditional resistance prediction methods, CFD technology has higher accuracy and is widely used.…”
Section: Introductionmentioning
confidence: 99%